COMMUNITY EMPOWERMENT THROUGH MARKETING OF HOUSEHOLD WASTE COMPOST IN SIMBE, MUTIARA TIMURDISTRICT, PIDIE REGENCY: PEMBERDAYAAN MASYARAKAT LEWAT PEMASARAN KOMPOS LIMBAH RUMAH TANGGA DI SIMBE KECAMATAN MUTIARA TIMURKABUPATEN PIDIE - Mawardiana; Jumi Adela Wardiansyah; Karnilawati (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
The high demand for compost among agricultural businesses has created opportunities to sell compost made from household waste. The community in Gampong Simbe, Mutiara Timur District, Pidie Regency, has not yet utilized household waste for composting, which has prompted the community service team to conduct community service in this area. The activity involved observing the community service site, discussing the timing and technical aspects of the activity, and introducing compost fertilizer through counseling, guidance, and training in fertilizer production for homemakers, PKK groups, and youth organizations. This activity consisted of preparation, implementation, and evaluation of the program. During the implementation phase, training was provided on compost production, packaging methods, sales models, and the profits from compost sales. The results of this activity provided participants with knowledge about how to make compost fertilizer, how to sell it, and how to calculate profits from compost sales. This enabled participants to increase their family income through compost sales and protect the environment from household waste, which they had not previously been aware of.